All-solid-state battery and preparation method thereof

By combining alkenyl siloxane crosslinking agent with acrylate monomers in the preparation of all-solid state batteries, the wetting and structural stability problems caused by the large viscosity of acrylate monomers are solved, and the battery has small internal resistance, high first efficiency and excellent cycle performance are achieved.

CN120300288APending Publication Date: 2025-07-11ZHEJIANG ANGOTE ELECTRIC TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510454914.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-11
Publication Date
2025-07-11

AI Technical Summary

Technical Problem

In the prior art, acrylate monomers have a high viscosity when preparing all-solid-state batteries, which makes it difficult for the precursor solution to be uniformly wet, and the polymer solid electrolytes formed are unevenly distributed, resulting in high internal resistance of the battery, poor first-effect and circulation performance, and easy side reactions to produce gas, affecting battery performance.

Method used

Alkenyl siloxane-based crosslinking agent is used to combine with acrylate monomers to reduce the viscosity of the precursor solution, improve wetting properties, and form a polymer with structural stability through copolymerization, inhibit side reactions, and inhibit the production of HF gas by using silicon-oxygen bond reaction.

Benefits of technology

The prepared all-solid state battery has small internal resistance, excellent first-effect and cycling performance, which improves the overall electrical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120300288A_ABST
    Figure CN120300288A_ABST
Patent Text Reader

Abstract

The invention provides an all-solid-state battery and a preparation method thereof, and belongs to the technical field of all-solid-state battery manufacturing. The preparation method of the all-solid-state battery comprises the following steps: providing a naked battery cell, the naked battery cell comprises an electrode assembly and a shell, the electrode assembly is accommodated in the shell, the electrode assembly comprises a positive plate, a diaphragm and a negative plate, and the diaphragm is located between the positive plate and the negative plate; under the vacuum condition, a precursor solution is injected into the shell, the precursor solution comprises an alkenyl siloxane cross-linking agent, an acrylate monomer, an initiator, a lithium salt and an organic solvent, then sealing treatment, standing treatment and heating treatment are conducted in sequence, the precursor solution is subjected to in-situ curing to form a polymer solid electrolyte, and the all-solid-state battery is obtained. The all-solid-state battery prepared by the preparation method has relatively low internal resistance and relatively excellent first effect and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of all-solid-state battery manufacturing, and more specifically, to an all-solid-state battery and a method for preparing the same. Background Art

[0002] Polymer solid electrolytes have advantages such as high mechanical strength, good electrochemical stability, and good thermal stability. At the same time, they have good compatibility with both low-voltage negative electrodes and high-voltage positive electrodes, which can improve the safety performance and energy density of lithium batteries. On this basis, in order to make the polymer solid electrolyte have a closer interfacial contact with the electrode sheet, and thus enable the corresponding battery to simultaneously have advantages such as high safety, long cycle life, and high energy density, researchers have proposed an in-situ curing process, that is, first transfer the bare battery cell into the housing, and then inject the precursor solution of the polymer solid electrolyte into the housing and successively go through steps such as sealing, standing, and heating, so that the precursor solution is in-situ cured to form a polymer solid electrolyte. Currently, acrylate monomers are one of the commonly used monomers for forming polymer solid electrolytes. However, there are problems such as the large viscosity of itself resulting in uneven distribution of the formed polymer solid electrolyte and the polymer formed by acrylate monomers being prone to side reactions during the charge and discharge process of the battery, resulting in serious gas generation (such as CO or CO2, etc.), which in turn leads to problems such as large internal resistance, poor initial efficiency, and cycle performance of the battery prepared by the in-situ curing process. Summary of the Invention

[0003] The purpose of this application is to provide an all-solid-state battery and a method for preparing the same. The all-solid-state battery prepared by this preparation method has both a relatively small internal resistance and relatively excellent initial efficiency and cycle performance.

[0004] The embodiments of this application are implemented as follows:

[0005] In a first aspect, an embodiment of this application provides a method for preparing an all-solid-state battery, including the following steps:

[0006] Provide a bare battery cell. The bare battery cell includes an electrode assembly and a housing. The electrode assembly is accommodated in the housing. The electrode assembly includes a positive electrode sheet, a separator, and a negative electrode sheet. The separator is located between the positive electrode sheet and the negative electrode sheet. Under a vacuum condition, inject a precursor solution into the housing. The precursor solution includes an alkenyl siloxane crosslinking agent, an acrylate monomer, an initiator, a lithium salt, and an organic solvent, and then successively perform a sealing treatment, a standing treatment, and a heating treatment to in-situ cure the precursor solution to form a polymer solid electrolyte, obtaining an all-solid-state battery.

[0007] In the prior art, acrylate monomers are one of the commonly used monomers for forming polymer solid electrolytes. However, the relatively high viscosity of these monomers makes it difficult for the corresponding precursor solution to effectively and uniformly infiltrate the bare battery cell, resulting in uneven distribution of the formed polymer solid electrolyte. The uneven distribution of the polymer solid electrolyte can lead to problems such as high internal resistance, poor initial efficiency, and cycling performance of the battery. In addition, the polymer formed only from acrylate monomers has poor structural stability, making it prone to side reactions during the charge and discharge process of the battery, resulting in serious gas generation inside the battery (such as CO or CO2, etc.). The serious gas generation can lead to an increase in the internal resistance of the battery and deterioration of the initial efficiency and cycling performance. In this application, based on the process of in-situ curing to form a polymer solid electrolyte, by compounding an alkenyl siloxane cross-linking agent and an acrylate monomer, on the one hand, adding the alkenyl siloxane cross-linking agent can reduce the viscosity of the precursor solution, thereby improving the wettability of the precursor solution to each functional component in the bare battery cell, so as to prepare a polymer solid electrolyte with a relatively uniform distribution. On the other hand, the polymer formed by copolymerization of the alkenyl siloxane cross-linking agent and the acrylate monomer has good structural stability, making it not easy to have side reactions during the charge and discharge process of the battery, thus being able to improve the gas generation problem caused by only using acrylate monomers. At the same time, the alkenyl siloxane cross-linking agent contains siloxane bonds, which can react with the HF gas (generated by side reactions of lithium salts) generated during the preparation and operation of the battery, and also helps to inhibit the adverse effects of gas generation on the battery. Through the combined action of these two aspects, the problems brought by the application of acrylate monomers in the in-situ curing process can be effectively solved, so that the prepared battery has both a relatively small internal resistance and excellent initial efficiency and cycling performance.

[0008] In some alternative embodiments, the alkenyl siloxane cross-linking agent is selected from at least one of vinyltris[(1-methylethenyl)oxy]silane, 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, 3-[[dimethyl(vinyl)silyl]oxy]-1,1,5,5-tetramethyl-3-phenyl-1,5-divinyltrisiloxane, and tetrakis(dimethylvinylsiloxy)silane.

[0009] In the above technical solution, by using the above types of alkenyl siloxane cross-linking agents, these alkenyl siloxane cross-linking agents have relatively rich branched-chain structures, and the overall structure is "multi-clawed". On the one hand, the "multi-clawed" alkenyl siloxane cross-linking agent can make the prepared polymer solid electrolyte have excellent structural stability. On the other hand, the "multi-clawed" alkenyl siloxane cross-linking agent can make the formed polymer solid electrolyte have a relatively rich pore structure, thus contributing to lithium ion transport. Through the combined action of these two aspects, the prepared battery can have more excellent comprehensive electrical properties.

[0010] In some alternative embodiments, the acrylate monomer is selected from at least one of diethylene glycol diacrylate, 1,5-pentanediol diacrylate, dipropylene glycol diacrylate, tri(ethylene glycol) diacrylate, ethylene glycol dimethacrylate, and polyethylene glycol diacrylate.

[0011] In the above technical solution, the applicable types of acrylate monomers are relatively rich, which can provide more alternative embodiments, thus facilitating the adaptive selection according to actual needs.

[0012] In some alternative embodiments, in the precursor solution, the molar ratio of the alkenyl siloxane crosslinker to the acrylate monomer is 1:(1 - 8).

[0013] In the above technical solution, limiting the molar ratio of the alkenyl siloxane crosslinker to the acrylate monomer within the above range helps to reduce the viscosity of the precursor solution. At the same time, it also helps the monomers to polymerize to form a polymer solid electrolyte.

[0014] In some alternative embodiments, in the precursor solution, the molar ratio of the alkenyl siloxane crosslinker to the acrylate monomer is 1:(2 - 6).

[0015] In the above technical solution, limiting the molar ratio of the alkenyl siloxane crosslinker to the acrylate monomer within a more suitable range is more conducive to reducing the viscosity of the precursor solution. At the same time, it can also make the reaction raw materials polymerize more thoroughly to form a polymer solid electrolyte, and then make the prepared battery have more excellent comprehensive electrical properties.

[0016] In some alternative embodiments, in the precursor solution, the sum of the mass percentages of the alkenyl siloxane crosslinker and the acrylate monomer is 6% - 15%.

[0017] In the above technical solution, limiting the sum of the mass percentages of the alkenyl siloxane crosslinker and the acrylate monomer in the precursor solution within the above range can make the precursor solution have a lower viscosity. At the same time, it can also make the raw material monomers polymerize more thoroughly to form a polymer solid electrolyte.

[0018] In some alternative embodiments, the material of the housing is an aluminum-plastic film. In the heat treatment step, it also includes a process of continuously applying pressure to the housing, where the pressure is 0.3 - 0.7 MPa.

[0019] In the above technical solution, the housing is made of aluminum-plastic film, that is, the battery is a soft-pack battery. For the soft-pack battery, in the heating treatment step, the pressure within the above range is continuously applied to the housing, so that the pressure inside the housing increases, which can further improve the uniformity of the distribution of the precursor solution, thereby preparing a more uniformly distributed polymer solid electrolyte, and further enabling the prepared battery to have more excellent comprehensive electrical properties.

[0020] In some alternative embodiments, in the standing treatment step, the standing time is 12 to 72 h.

[0021] In the above technical solution, limiting the duration in the standing treatment step within the above range helps the precursor solution to be fully and uniformly infiltrated, thereby preparing a polymer solid electrolyte with a relatively uniform distribution.

[0022] In some alternative embodiments, in the heating treatment step, the treatment temperature is 55 to 70 °C and the treatment time is 8 to 12 h.

[0023] In the above technical solution, jointly limiting the temperature and duration in the heating treatment step within the above range helps the reaction monomers to polymerize more thoroughly to form a polymer solid electrolyte.

[0024] In a second aspect, an embodiment of the present application provides a all-solid-state battery, which is prepared by using the preparation method of the all-solid-state battery provided in the embodiment of the first aspect.

[0025] In the above technical solution, the all-solid-state battery is prepared by using the preparation method of the all-solid-state battery provided in the embodiment of the first aspect. Since an alkenyl siloxane cross-linking agent is added to the precursor solution, on the one hand, adding the alkenyl siloxane cross-linking agent can reduce the viscosity of the precursor solution, thereby improving the wettability of the precursor solution to each functional component in the bare battery cell, so as to prepare a polymer solid electrolyte with a relatively uniform distribution; on the other hand, the polymer formed by the copolymerization of the alkenyl siloxane cross-linking agent and the acrylate monomer has good structural stability, so that the polymer is not prone to side reactions during the charge and discharge process of the battery, thereby being able to improve the gas generation problem caused by only using acrylate monomers; at the same time, the alkenyl siloxane cross-linking agent has a silicon-oxygen bond, which can react with the HF gas (generated by the side reaction of the lithium salt) generated during the preparation and operation of the battery, and also helps to inhibit the adverse effects of gas generation on the battery. Through the combined action of the two aspects, the problems brought about by the application of acrylate monomers in the in-situ curing process can be effectively solved, so that the prepared all-solid-state battery has both a relatively small internal resistance and relatively excellent initial efficiency and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] To more clearly illustrate the technical solutions of the embodiments of the present application, the following will briefly introduce the accompanying drawings required in the embodiments. It should be understood that the following drawings only show some embodiments of the present application and should not be regarded as limiting the scope. For those of ordinary skill in the art, without creative efforts, other related drawings can also be obtained based on these drawings.

[0027] Figure 1 Process flow chart of a preparation method of a all-solid-state battery provided by the present application;

[0028] Figure 2 Curing results of a series of precursor solutions provided by the present application;

[0029] Figure 3 Wetting results of a series of precursor solutions provided by the present application on the separator. Specific embodiments

[0030] To make the objectives, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below. Those not specified in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. Those reagents or instruments not specified by the manufacturer can all be obtained as conventional products through commercial purchase.

[0031] It should be noted that the "and / or" in the present application, such as "feature 1 and / or feature 2", refers to the three cases of "feature 1" alone, "feature 2" alone, and "feature 1" plus "feature 2".

[0032] In addition, in the description of the present application, unless otherwise specified, the "multiple" in "one or more" means two or more; the range of "numerical value a to numerical value b" includes the two end values "a" and "b", and the "measurement unit" in "numerical value a to numerical value b + measurement unit" represents the "measurement unit" of both "numerical value a" and "numerical value b".

[0033] The following specifically describes an all-solid-state battery, its preparation method and an electrical device according to the embodiments of the present application.

[0034] In a first aspect, the embodiments of the present application provide a preparation method of an all-solid-state battery, including the following steps:

[0035] A bare battery cell is provided. The bare battery cell includes an electrode assembly and a housing. The electrode assembly is accommodated in the housing. The electrode assembly includes a positive electrode sheet, a separator, and a negative electrode sheet, and the separator is located between the positive electrode sheet and the negative electrode sheet; under a vacuum condition, a precursor solution is injected into the housing, where the precursor solution includes a vinyl siloxane crosslinking agent, an acrylate monomer, an initiator, a lithium salt, and an organic solvent, and then a sealing treatment, a standing treatment, and a heating treatment are sequentially performed to in-situ cure the precursor solution to form a polymer solid electrolyte, thereby obtaining a all-solid-state battery.

[0036] In the prior art, acrylate monomers are one of the commonly used monomers for forming polymer solid electrolytes. However, the relatively high viscosity of this monomer makes it difficult for the corresponding precursor solution to effectively and uniformly infiltrate the bare battery cell, which in turn leads to uneven distribution of the formed polymer solid electrolyte. The uneven distribution of the polymer solid electrolyte will cause problems such as high internal resistance, poor initial efficiency, and poor cycling performance of the battery; in addition, the polymer formed only by acrylate monomers has a problem of poor structural stability, which makes side reactions likely to occur during the charge and discharge process of the battery, resulting in serious gas generation inside the battery (such as CO or CO2, etc.). Serious gas generation will cause an increase in the internal resistance of the battery and deterioration of the initial efficiency and cycling performance. In this application, based on the process of in-situ curing to form a polymer solid electrolyte, by compounding and using a vinyl siloxane crosslinking agent and an acrylate monomer, on the one hand, adding the vinyl siloxane crosslinking agent can reduce the viscosity of the precursor solution, thereby improving the wettability of the precursor solution to each functional component in the bare battery cell, so as to prepare a polymer solid electrolyte with a relatively uniform distribution; on the other hand, the polymer formed by copolymerization of the vinyl siloxane crosslinking agent and the acrylate monomer has good structural stability, so that the polymer is not likely to undergo side reactions during the charge and discharge process of the battery, thereby being able to improve the gas generation problem caused by only using acrylate monomers; at the same time, the vinyl siloxane crosslinking agent has a silicon-oxygen bond, which can react with HF gas (generated by side reactions of lithium salts) generated during the preparation and operation of the battery, and also helps to inhibit the adverse effects of gas generation on the battery. Through the combined action of the two aspects, the problems brought about by the application of acrylate monomers in the in-situ curing process can be effectively solved, so that the prepared battery has both a relatively small internal resistance and relatively excellent initial efficiency and cycling performance.

[0037] It should be noted that the form of the battery cell is not limited. For example, it can be a wound battery cell or a stacked battery cell. In this embodiment of the application, a stacked battery cell is taken as an example.

[0038] It should be noted that functional components such as the electrode sheets and the separator in the battery cell can be set according to the conventional selection in the art.

[0039] As an example, the negative active material in the negative electrode sheet is selected from at least one of graphite, silicon, silicon-carbon, and silicon-oxy-carbon.

[0040] As an example, the cathode active material in the cathode sheet is selected from at least one of lithium iron phosphate, lithium cobaltate, lithium manganate, lithium nickel manganate, ternary nickel cobalt manganese, and ternary nickel cobalt aluminum.

[0041] As an example, the conductive agent is selected from at least one of conductive carbon black, acetylene black, VGCF, and carbon nanotubes.

[0042] As an example, the binder is selected from at least one of polyvinylidene fluoride, polyacrylic acid, sodium carboxymethyl cellulose, and styrene-butadiene rubber.

[0043] As an example, the material of the separator is selected from at least one of PP and PE.

[0044] It should be noted that the types of various functional components in the precursor solution are not limited.

[0045] As an example, the alkenyl siloxane crosslinking agent is selected from at least one of vinyltris[(1-methylethenyl)oxy]silane, 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, 3-[[dimethyl(vinyl)silyl]oxy]-1,1,5,5-tetramethyl-3-phenyl-1,5-divinyltrisiloxane, and tetrakis(dimethylvinylsiloxy)silane.

[0046] In this embodiment, the above types of alkenyl siloxane crosslinking agents are used. These alkenyl siloxane crosslinking agents have relatively rich branched-chain structures, and the overall structure is "multi-clawed". On the one hand, the "multi-clawed" alkenyl siloxane crosslinking agent can make the prepared polymer solid electrolyte have excellent structural stability; on the other hand, the "multi-clawed" alkenyl siloxane crosslinking agent can make the formed polymer solid electrolyte have relatively rich pore structures, thus contributing to lithium ion transmission. Through the combined action of the two aspects, the prepared battery can have more excellent comprehensive electrical properties.

[0047] To better understand the technical solution, the structural formulas of the above four alkenyl siloxane crosslinking agents are used here for auxiliary explanation. Specifically, please refer to the following formulas (a) to (d) in sequence:

[0048]

[0049] As an example, the acrylate monomer is selected from at least one of diethylene glycol diacrylate, 1,5-pentanediol diacrylate, dipropylene glycol diacrylate, tris(ethylene glycol) diacrylate, ethylene glycol dimethacrylate, and polyethylene glycol diacrylate.

[0050] In this embodiment, there is a relatively rich variety of applicable acrylate monomers, which can provide more implementation schemes, facilitating adaptive selection according to actual needs.

[0051] As an example, the initiator includes azobisisobutyronitrile.

[0052] As an example, the lithium salt is selected from at least one of lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and lithium difluoro(oxalato)borate (LiODFB).

[0053] As an example, the organic solvent is selected from at least one of ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), vinylene carbonate (VC), and fluoroethylene carbonate (FEC).

[0054] As an example, in the precursor solution, the molar ratio of the alkenyl siloxane crosslinker to the acrylate monomer is 1:(1 - 8), such as, but not limited to, any one of the point values of 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, and 1:8 or the range values between any two of them.

[0055] In this embodiment, limiting the molar ratio of the alkenyl siloxane crosslinker to the acrylate monomer within the above range helps to reduce the viscosity of the precursor solution. At the same time, it also helps the monomer to polymerize to form a polymer solid electrolyte.

[0056] As an example, in the precursor solution, the molar ratio of the alkenyl siloxane crosslinker to the acrylate monomer is 1:(2 - 6), such as, but not limited to, any one of the point values of 1:2, 1:3, 1:4, 1:5, and 1:6 or the range values between any two of them.

[0057] In this embodiment, limiting the molar ratio of the alkenyl siloxane crosslinker to the acrylate monomer within a more suitable range is more conducive to reducing the viscosity of the precursor solution. At the same time, it can also enable the reaction raw materials to polymerize more thoroughly to form a polymer solid electrolyte, and thus the prepared battery has more excellent comprehensive electrical properties.

[0058] It should be noted that the mass percentage of each functional component in the precursor solution is not limited and can be adaptively adjusted according to actual needs.

[0059] As an example, in the precursor solution, the sum of the mass percentages of the alkenyl siloxane crosslinking agent and the acrylate monomer is 6% to 15%, for example, but not limited to, any one of the point values of 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, and 15% or the range values between any two of them.

[0060] In this embodiment, the sum of the mass percentages of the alkenyl siloxane crosslinking agent and the acrylate monomer in the precursor solution is limited to the above range, so that the precursor solution has a lower viscosity. At the same time, it can also make the raw material monomers polymerize more thoroughly to form a polymer solid electrolyte.

[0061] As an example, by mass percentage, the precursor solution includes: 0.1% to 0.5% of an initiator, 10 to 20% of a lithium salt, and the balance of an organic solvent.

[0062] As an example, the material of the shell is an aluminum-plastic film. In the heating treatment step, a process of continuously applying pressure to the shell is also included, where the pressure is 0.3 to 0.7 MPa, for example, but not limited to, any one of the point values of 0.3 MPa, 0.4 MPa, 0.5 MPa, 0.6 MPa, and 0.7 MPa or the range values between any two of them.

[0063] In this embodiment, the material of the shell is an aluminum-plastic film, that is, the battery is a soft-pack battery. For a soft-pack battery, in the heating treatment step, the above range of pressure is continuously applied to the shell, so that the pressure inside the shell increases, which can further improve the distribution uniformity of the precursor solution, thereby preparing a polymer solid electrolyte with a more uniform distribution, and further making the prepared battery have more excellent comprehensive electrical properties.

[0064] As an example, in the static treatment step, the static time is 12 to 72 h, for example, but not limited to, any one of the point values of 12 h, 20 h, 30 h, 40 h, 50 h, 60 h, 70 h, and 72 h or the range values between any two of them.

[0065] In this embodiment, the duration of the static treatment step is limited to the above range, which helps the precursor solution to be fully and uniformly infiltrated, thereby preparing a polymer solid electrolyte with a more uniform distribution.

[0066] As an example, in the heating treatment step, the treatment temperature is 55 to 70 °C, for example, but not limited to, any one of the point values of 55 °C, 60 °C, 65 °C, and 70 °C or the range values between any two of them; the treatment time is 8 to 12 h, for example, but not limited to, any one of the point values of 8 h, 9 h, 10 h, 11 h, and 12 h or the range values between any two of them.

[0067] In this embodiment, restricting the temperature and duration in the heat treatment step within the above ranges helps the reaction monomers to polymerize more thoroughly to form a polymer solid electrolyte.

[0068] It should be noted that for the processes or steps not specifically described in the preparation process, they can be set according to the conventional selection in the art.

[0069] As an example, the process flow chart of the preparation method of the all-solid-state battery can be referred to Figure 1 .

[0070] To better understand the technical solution, an auxiliary description is given here in combination with a polymerization schematic diagram of the monomer. Specifically, see Formula I, where the alkenyl siloxane cross-linking agent is vinyl tris[(1-methylethenyl)oxy]silane, and the acrylate monomer is ethylene glycol diacrylate monomer.

[0071]

[0072] In a second aspect, an all-solid-state battery provided by an embodiment of the present application is prepared by using the preparation method of the all-solid-state battery provided in the first aspect.

[0073] In the present application, the all-solid-state battery is prepared by using the preparation method of the all-solid-state battery provided in the first aspect. Since an alkenyl siloxane cross-linking agent is added to the precursor solution, on the one hand, adding the alkenyl siloxane cross-linking agent can reduce the viscosity of the precursor solution, thereby improving the wettability of the precursor solution to each functional component in the bare battery cell, so as to prepare a polymer solid electrolyte with a more uniform distribution; on the other hand, the polymer formed by copolymerization of the alkenyl siloxane cross-linking agent and the acrylate monomer has good structural stability, so that the polymer is not prone to side reactions during the charge and discharge process of the battery, thereby being able to improve the gas generation problem caused by only using the acrylate monomer; at the same time, the alkenyl siloxane cross-linking agent has a silicon-oxygen bond, which can react with the HF gas (generated by the side reaction of the lithium salt) generated during the preparation and operation of the battery, and also helps to inhibit the adverse effects of gas generation on the battery. Through the combined action of the two aspects, the problems brought about by the application of acrylate monomers in the in-situ curing process can be effectively solved, so that the prepared all-solid-state battery has both a smaller internal resistance and relatively excellent initial efficiency and cycle performance.

[0074] The features and performance of the present application are further described in detail below in conjunction with embodiments.

[0075] Example 1

[0076] An embodiment of the present application provides a preparation method of an all-solid-state battery, including the following steps:

[0077] S1 Battery cell preparation

[0078] By mass percentage, 97% of lithium iron phosphate (cathode active material), 1.5% of conductive carbon black (conductive agent), and 1.5% of polyvinylidene fluoride (binder) are dispersed in N-methyl-2-pyrrolidone to obtain a cathode slurry; then, the cathode slurry is evenly coated on both sides of the aluminum foil; then, through drying, calendaring, and vacuum drying in sequence, and after welding an aluminum lead wire with an ultrasonic welder, a cathode plate with a thickness of 125 μm is obtained.

[0079] By mass percentage, 94.5% of graphite (anode active material), 1.5% of conductive carbon black (conductive agent), 3.5% of carboxymethyl cellulose (binder), and 0.5% of styrene-butadiene rubber (binder) are dispersed in deionized water to obtain an anode slurry; then, the anode slurry is coated on both sides of the copper foil; then, through drying, calendaring, and vacuum drying in sequence, and after welding a nickel lead wire with an ultrasonic welder, an anode plate with a thickness of 125 μm is obtained.

[0080] The prepared cathode plate, PP separator, and anode plate are stacked in sequence, and then put into an aluminum-plastic film casing for welding and encapsulation to obtain a bare battery cell.

[0081] S2 Battery Preparation

[0082] By mass percentage, vinyltris[(1-methylethenyl)oxy]silane and ethylene glycol diacrylate monomers with a molar ratio of 1:8 (the sum of their mass ratios is 10%), 0.1% of azobisisobutyronitrile (initiator), 10% of lithium hexafluorophosphate (lithium salt), and 79.9% of ethylene carbonate (organic solvent) are mixed evenly to obtain a precursor solution.

[0083] Under vacuum conditions, the precursor solution is injected into the casing (the injection volume is 8 g); then, sealing treatment, standing treatment, and heating treatment are carried out in sequence. Among them, in the standing treatment step, it stands at room temperature for 48 h; in the heating treatment step, a pressure of 0.5 MPa is continuously applied to the casing and heat preservation treatment is carried out at 60 °C for 8 h to in-situ cure the precursor solution to form a polymer solid electrolyte, obtaining a all-solid-state soft-pack battery with a capacity of 2 Ah, and obtaining an all-solid-state battery.

[0084] Example 2

[0085] The embodiment of the present application provides a preparation method of an all-solid-state battery, and the difference from Example 1 is only that: the molar ratio of vinyltris[(1-methylethenyl)oxy]silane to ethylene glycol diacrylate is 1:6.

[0086] Example 3

[0087] An embodiment of the present application provides a method for preparing an all-solid-state battery, which is only different from Embodiment 1 in that the molar ratio of vinyltris[(1-methylethenyl)oxy]silane to ethylene glycol diacrylate is 1:4.

[0088] Example 4

[0089] An embodiment of the present application provides a method for preparing an all-solid-state battery, which is only different from Embodiment 1 in that the molar ratio of vinyltris[(1-methylethenyl)oxy]silane to ethylene glycol diacrylate is 1:2.

[0090] Example 5

[0091] An embodiment of the present application provides a method for preparing an all-solid-state battery, which is only different from Embodiment 1 in that the molar ratio of vinyltris[(1-methylethenyl)oxy]silane to ethylene glycol diacrylate is 1:1.

[0092] Comparative Example 1

[0093] The comparative example of the present application provides a method for preparing an all-solid-state battery, which is only different from Embodiment 1 in that the precursor solution does not contain vinyltris[(1-methylethenyl)oxy]silane.

[0094] Comparative Example 2

[0095] The comparative example of the present application provides a method for preparing an all-solid-state battery, which is only different from Embodiment 1 in that all of the vinyltris[(1-methylethenyl)oxy]silane is replaced with triallyl isocyanurate.

[0096] Test Example

[0097] (1) Curing performance test of the precursor solution

[0098] Test method:

[0099] The precursor solutions in Examples 1 to 5 were numbered and used as specimens respectively, then kept at 60 °C for 8 h, and then the curing conditions of each sample were compared and photographed.

[0100] Refer to Figure 2 , which correspond to Examples 1 to 5 from left to right one by one. From the test results of Examples 1 to 5, it can be seen that when the molar ratio of vinyltris[(1-methylethenyl)oxy]silane to ethylene glycol diacrylate is limited within the range of 1:(2-6), compared with not within this range, the former can make the reaction raw materials polymerize more thoroughly to form a polymer solid electrolyte (the mass of the white solid at the bottom of the bottles in Examples 2 to 4 is more).

[0101] (2) Wetting performance test of the precursor solution

[0102] The precursor solutions in Examples 1 to 5 and Comparative Example 1 were numbered respectively and used as samples, and then the contact angles of each sample on the PP separator were measured. Among them, the contact angle was measured by the goniometry method.

[0103] Refer to Figure 3 , it can be seen from the test results of Examples 1 to 5 and Comparative Example 1 that when the vinyltris[(1-methylethenyl)oxy]silane crosslinking agent is added to the precursor solution, compared with the case where the vinyltris[(1-methylethenyl)oxy]silane crosslinking agent is not added, the angle of the contact angle of the former is smaller, indicating that adding the vinyltris[(1-methylethenyl)oxy]silane crosslinking agent to the precursor solution can effectively reduce the viscosity of the precursor solution, thereby improving the wettability of the precursor solution on the separator.

[0104] It can be seen from the test results of Examples 1 to 5 that when the molar ratio of vinyltris[(1-methylethenyl)oxy]silane to ethylene glycol diacrylate is limited within the range of 1:(2 - 6), compared with not within this range, the angle of the contact angle of the former is smaller, indicating that adding the vinyltris[(1-methylethenyl)oxy]silane crosslinking agent to the precursor solution can effectively reduce the viscosity of the precursor solution, thereby improving the wettability of the precursor solution on the separator.

[0105] (3) Performance test of all-solid-state battery

[0106] Test method:

[0107] The batteries prepared in Examples 1 to 5 and Comparative Examples 1 to 2 were numbered respectively. At the same time, the battery prepared with a commercial electrolyte (LBC338 lithium iron phosphate electrolyte from Capchem) was used as a control group. The only difference between the control group and Example 1 was that the precursor solution was completely replaced with the commercial electrolyte. Then, an internal resistance voltage meter was used to measure the internal resistance (mΩ) of each sample, and a Neware battery test system was used to measure the 0.05C initial efficiency (%) and the capacity retention rate (%) after 300 cycles at 0.5C of each sample. Then, the test results were tabulated in Table 1.

[0108] Among them, the test steps for the internal resistance are as follows:

[0109] The red and black connectors of the internal resistance voltage meter were connected to the positive and negative electrodes of the battery respectively, and the internal resistance of the battery was measured and recorded.

[0110] The test steps for the 0.05C initial efficiency are as follows:

[0111] The battery was placed at 25°C, and the battery was subjected to one charge-discharge cycle at a current of 0.05C in the charge-discharge voltage range of 2.5 - 3.65V. The first charge capacity and the first discharge capacity were recorded. The first discharge efficiency (initial efficiency) = first discharge capacity / first charge capacity × 100%.

[0112] The test steps for the capacity retention rate after 300 cycles at 0.5C are as follows:

[0113] Place the battery at 25°C. The battery is charged and discharged in a voltage range of 2.5 - 3.65V using a 0.5C current for charge and discharge cycles. Record the discharge capacities of the 1st cycle and the 300th cycle. The capacity retention rate after 300 cycles (%) = (discharge capacity of the 300th cycle / discharge capacity of the 1st cycle) × 100%.

[0114] Table 1

[0115] Sample Internal resistance / mΩ Initial efficiency / % Capacity retention rate after 300 cycles at 0.5C / % Example 1 11.978 87.29 95.23 Example 2 10.801 89.99 99.82 Example 3 10.968 89.54 98.88 Example 4 11.378 88.13 96.35 Example 5 11.888 87.79 95.88 Comparative Example 1 12.798 86.47 93.87 Comparative Example 2 13.578 85.69 91.88 Control group 10.673 90.03 99.85

[0116] Referring to Table 1, from the test results of Examples 1 - 5 and Comparative Example 1, when an alkenyl siloxane cross - linker is added to the precursor solution, compared with the case without adding an alkenyl siloxane cross - linker, the corresponding battery has both a smaller internal resistance and more excellent initial efficiency and cycling performance.

[0117] From the test results of Examples 1 - 5 and Comparative Example 2, it can be seen that when an alkenyl siloxane cross - linker is added to the precursor solution, compared with using other types of cross - linkers, the corresponding battery has both a smaller internal resistance and more excellent initial efficiency and cycling performance.

[0118] From the test results of Examples 1 - 5, when the molar ratio of the alkenyl siloxane cross - linker to the acrylate monomer is limited within the range of 1:(2 - 6), compared with not being in this range, the corresponding battery has both a smaller internal resistance and more excellent initial efficiency and cycling performance; among them, when the molar ratio of the alkenyl siloxane cross - linker to the acrylate monomer is limited to 1:6, the comprehensive electrical properties of the corresponding battery are the best.

[0119] From the test results of Example 2 and the control group, when the molar ratio of the alkenyl siloxane cross - linker to the acrylate monomer is limited to 1:6, the comprehensive electrical properties of the corresponding all - solid - state battery are comparable to those of a conventional non - all - solid - state battery using a commercial electrolyte. However, compared with the battery using a commercial electrolyte, the all - solid - state battery provided in this application has more advantages in terms of safety.

[0120] The embodiments described above are some, but not all, of the embodiments of this application. The detailed description of the embodiments of this application is not intended to limit the scope of this application that is claimed, but merely represents the selected embodiments of this application. All other embodiments obtained by those of ordinary skill in the art based on the embodiments in this application without creative efforts fall within the scope of protection of this application.

Claims

1. A method for preparing an all-solid-state battery, characterized in that, The method includes the following steps: Providing a bare battery cell, the bare battery cell including an electrode assembly and a housing, the electrode assembly being accommodated in the housing, the electrode assembly including a positive electrode sheet, a separator, and a negative electrode sheet, the separator being located between the positive electrode sheet and the negative electrode sheet; Injecting a precursor solution into the housing under a vacuum condition, wherein the precursor solution includes a vinyl siloxane crosslinking agent, an acrylate monomer, an initiator, a lithium salt, and an organic solvent, and then successively performing a sealing treatment, a standing treatment, and a heating treatment to in-situ cure the precursor solution to form a polymer solid electrolyte, thereby obtaining a all-solid-state battery.

2. The preparation method of the all-solid-state battery according to claim 1, characterized in that, The vinyl siloxane crosslinking agent is selected from at least one of vinyltris[(1-methylethenyl)oxy]silane, 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, 3-[[dimethyl(vinyl)silyl]oxy]-1,1,5,5-tetramethyl-3-phenyl-1,5-divinyltrisiloxane, and tetrakis(dimethylethoxysilyl)silane.

3. The preparation method of the all-solid-state battery according to claim 2, wherein The acrylate monomer is selected from at least one of diethylene glycol diacrylate, 1,5-pentanediol diacrylate, dipropylene glycol diacrylate, tri(ethylene glycol) diacrylate, ethylene glycol dimethacrylate, and polyethylene glycol diacrylate.

4. The method for preparing an all-solid-state battery according to claim 3, wherein, In the precursor solution, the molar ratio of the vinyl siloxane crosslinking agent to the acrylate monomer is 1:(1-8).

5. The method for preparing an all-solid-state battery according to claim 4, wherein, The molar ratio of the vinyl siloxane crosslinking agent to the acrylate monomer is 1:(2-6).

6. The preparation method of the all-solid-state battery according to any one of claims 1 to 5, characterized in that, In the precursor solution, the sum of the mass percentages of the vinyl siloxane crosslinking agent and the acrylate monomer is 6%-15%.

7. The manufacturing method of the all-solid-state battery according to any one of claims 1 to 5, characterized in that The material of the housing is an aluminum-plastic film. In the heating treatment step, a process of continuously applying pressure to the housing is further included, wherein the pressure is 0.3-0.7 MPa.

8. The preparation method of the all-solid-state battery according to any one of claims 1 to 5, characterized in that, In the standing treatment step, the standing time is 12-72 h.

9. The preparation method of the all-solid-state battery according to any one of claims 1 to 5, characterized in that, In the heating treatment step, the treatment temperature is 55-70 °C, and the treatment time is 8-12 h.

10. A all-solid-state battery, characterized in that, Prepared by using the preparation method of the all-solid-state battery according to any one of claims 1-9.

Citation Information

Cited By

  • Secondary battery and preparation method thereof, energy storage system and electric equipment

    CN120955193A